(untitled) (Research, Society and Development, 2022)
Emotional eating refers to the urge to eat as a reaction to stressors or euphoria in the face of emotions of sadness and fear. Coping skill deficit levels predict binge eating behaviors. The objective of this research was to identify the psychological interventions used by psychologists in the treatment of obesity. This is an integrative review that began with consultation of the Health Sciences descriptors (DeCS), through the VHL and Publisher Medline (PUBMED), with the following controlled descriptors: "Cognitive Behavioral Therapy", "Dialectial Behavior Therapy", “Dialectial Behavioral Therapy”, “Behavior Therapy” and “Obesity” with the Boolean operators “OR” and “AND”. At the end of the searches, 13 publications met the analysis criteria and were selected for the study. In view of the selected studies, we found 4 interventions divided into categories: emotional regulation, Mindful eating, cognitive restructuring and contingency management. The study showed, through the findings, that the psychological interventions found in this study are fundamental for the treatment of the obese person, to overcome the difficulties that these patients find in weight control, as these are important interventions for the psychologist in the care of the different health care settings.